2010
DOI: 10.1021/jp101852y
|View full text |Cite
|
Sign up to set email alerts
|

Sn/SnOx Core−Shell Nanospheres: Synthesis, Anode Performance in Li Ion Batteries, and Superconductivity

Abstract: Sn/SnO x core-shell nanospheres have been synthesized via a modified polyol process. Their size can be readily controlled by tuning the usage of surface stabilizers and the temperature. Anode performance in Li ion batteries and their superconducting properties is detailed. As anode materials, 45 nm nanospheres outperform both larger and smaller ones. Thus, they exhibit a capacity of about 3443 mAh cm -3 and retain about 88% of after 10 cycles. We propose a model based on the microstructural evolution to explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 58 publications
4
73
0
Order By: Relevance
“…1(a) and (b) show that the electrode using CMC displays a much higher current density than that of using PVdF in the initial cycle, and the current density maintains stable in the following two cycles, indicating better cyclic retention of the electrode using CMC. In the case of CMC, the peak around 1.0 V in the cathodic process may involve three parts: the reduction of the electrolyte to form an SEI (solid electrolyte interface) film, the reduction of tin oxide that formed when the electrodes were exposed in the air during the preparation of the electrodes [26], and some reductive reactions of CMC. El Ouatani et al [22] found that the chemical reactivity of CMC towards the electrolyte takes part in the formation of the surface film, and contributes to the good properties of CMC as binder, and the reaction of CMC towards the electrolyte do not disappear upon electrochemical cycling.…”
Section: Resultsmentioning
confidence: 99%
“…1(a) and (b) show that the electrode using CMC displays a much higher current density than that of using PVdF in the initial cycle, and the current density maintains stable in the following two cycles, indicating better cyclic retention of the electrode using CMC. In the case of CMC, the peak around 1.0 V in the cathodic process may involve three parts: the reduction of the electrolyte to form an SEI (solid electrolyte interface) film, the reduction of tin oxide that formed when the electrodes were exposed in the air during the preparation of the electrodes [26], and some reductive reactions of CMC. El Ouatani et al [22] found that the chemical reactivity of CMC towards the electrolyte takes part in the formation of the surface film, and contributes to the good properties of CMC as binder, and the reaction of CMC towards the electrolyte do not disappear upon electrochemical cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Though the capacity decreases with the higher rate, the synthesized product exhibits a stable cycle capability. Compared with the previous reported SnO 2 /graphene hybridization [29] and coreeshell structures SnO 2 materials [7,8], the material reported here is very attractive due to its facile, economical, and improved lithium storage. Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Wang et al successfully synthesized a series of M-Sn (M=Fe, Cu, Co, Ni) nanospheres [97] with size of 30~50 nm by a conversion chemistry, [98][99][100] which could rigorously control both the shape and the size of these nanoparticles for comparing their different performances. The theoretical capacities are CoSn 3 (852 M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT mAh g −1 ) > FeSn 2 (804 mAh g −1 ) > Ni 3 Sn 4 (725 mAh g −1 ) > Cu 6 Sn 5 (605 mAh g −1 ).…”
Section: High-capacity Sn-based Anodesmentioning
confidence: 99%